A comparison of healthcare resource use for rotavirus and RSV between vulnerable children with co-morbidities and healthy children: a case control study. Issue 4 (April 2013) - Pockett, Rhys D.; Campbell, David; Carroll, Stuart; Rajoriya, Fiona; Adlard, Nick
Abstract Objective: To quantify the differences in hospital length of stay (LOS) and cost between healthy and vulnerable children with cystic fibrosis (CF), insulin-dependent diabetes mellitus (IDDM), cancer, and epilepsy who contract rotavirus (RVGE) or respiratory syncytial virus (RSV). Methods: Hospital Episode Statistics (HES) data were collected for England, for children <5 years old, admitted between April 2001 and March 2008, using ICD-10 codes for RVGE and RSV. Cases were identified as having RVGE and/or RSV plus CF, IDDM, cancer, or epilepsy. Healthy controls had RVGE and/or RSV only, additional controls had eczema only. Cost, hospital LOS, and demographics were collected. Results: Four hundred and eighty-six (0.5%) cases and 101, 784 (99.5%) healthy controls were admitted with RVGE or RSV, with 17, 420 eczema controls. RVGE was present in 153 (31.5%) cases and 7532 (7.4%) healthy controls, and RSV in 333 (68.5%) cases and 94, 252 (92.6%) healthy controls. Cases were older (1.1 years, SD = 1.3 years), had greater LOS (9.9 days, SD = 19.9), and cost more (£3477, SD = £7765) than healthy controls (age = 0.2, SD = 0.5, p < 0.001; LOS = 1.9 days, SD = 3.1, p < 0.001; cost = £595, SD = £727, p < 0.001). Cost for cases was 6-times greater than healthy controls (p < 0.001). Controls had a 0.3 day greater LOS (p < 0.001) with RSV, but a £17 (p = 0.085) lower mean cost than RVGE. Conclusion: RVGE and RSV are more serious diseases in vulnerable children, requiring more intense resource use. The importance of preventing infection in vulnerable children is underlined by hygiene and appropriate isolation and vaccination strategies. When universal vaccination is under consideration, as for rotavirus vaccines, evaluation of a vaccination programme should consider the potentially positive impact on vulnerable children. Limitations: Limitations of the study include a dependency on accurate coding, an expectation that patients are identified through laboratory testing, and the possibility of unidentified underlying conditions affecting the burden.